EXPLORING A THREE-LEVEL TEACHING MODEL FOR INTEGRATING ADVERTISING DESIGN COMPETITIONS IN HIGHER EDUCATION: A PEDAGOGICAL APPROACH - Li, Jinghe; Mastika, Lamat (Global Academic Excellence (M) Sdn Bhd (GAE), 2025)
As the demands for innovation and practical skills in advertising design education continue to grow, traditional teaching models can no longer meet the requirements of modern design education. This paper proposes and explores a three-levelteaching model based on the integration of competition and education. The model incorporates advertising design competitions into the teaching process and is divided into three stages: theoretical learning and basic design training,decompositionof competition projectsand simulation training, and actual competition and projectreview.The study demonstrates that this model effectively enhances students' creativity and practical skills while optimizing teaching methods and outcomes. By implementing this model, students refine their design skills in real competition environments, with significant improvements in creative abilities. At the same time, teachers can provide timely feedback and make adjustments based on students’ performance.This paper further analyzes the application of the model through specific teaching cases and discusses its potential for broader application in other design courses. The findings offer new perspectives for innovation and development in design education and propose recommendations for futureteaching reforms and related research.